2014
DOI: 10.1186/s12953-014-0047-0
|View full text |Cite
|
Sign up to set email alerts
|

Potential serum biomarkers for glioblastoma diagnostic assessed by proteomic approaches

Abstract: BackgroundThe rapid progress of proteomics over the past years has allowed the discovery of a large number of potential biomarker candidates to improve early tumor diagnosis and therapeutic response, thus being further integrated into clinical environment. High grade gliomas represent one of the most aggressive and treatment-resistant types of human brain cancer, with approximately 9–12 months median survival rate for patients with grade IV glioma (glioblastoma). Using state-of-the-art proteomics technologies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 63 publications
1
33
0
Order By: Relevance
“…Further, YKL40 and MMP9 levels in sera from post-operative period were found reduced in patients with no radiographic evidence of disease suggesting their utility in treatment monitoring [41]. Recently, using Surface-enhanced laser desorption/ionization timeof-flight mass spectrometry (SELDI-TOF) proteomic approach three molecules namely-S100A8, S100A9 and CXCL4 were identified as putative biomarkers for GBM [43]. Serum level of B-chain of α 2 -Heremans-Schmid glycoprotein (AHSG) was found to be decreased in majority of the GBM samples when compared to normal samples and had a good prognostic value [44].…”
Section: Discussionmentioning
confidence: 99%
“…Further, YKL40 and MMP9 levels in sera from post-operative period were found reduced in patients with no radiographic evidence of disease suggesting their utility in treatment monitoring [41]. Recently, using Surface-enhanced laser desorption/ionization timeof-flight mass spectrometry (SELDI-TOF) proteomic approach three molecules namely-S100A8, S100A9 and CXCL4 were identified as putative biomarkers for GBM [43]. Serum level of B-chain of α 2 -Heremans-Schmid glycoprotein (AHSG) was found to be decreased in majority of the GBM samples when compared to normal samples and had a good prognostic value [44].…”
Section: Discussionmentioning
confidence: 99%
“…2D/DIGE represents a “common” approach in the discovery of PCa biomarkers, using as starting material serum, plasma, tissue samples from patients, as well as various cell cultures featuring the cancers under observation [27]. Using the 2D-DIGE approach, 118 proteins with significantly altered expression were identified by Ummanni et al in prostatic tissue tumor vs .…”
Section: Proteomics Discovery Platforms Used In Prostate Cancer Biomamentioning
confidence: 99%
“…Simultaneous evaluation of multiple proteins in serum and cerebrospinal fluid allows for the identification of novel circulating biomarker panels helpful in disease diagnosis and treatment [4]. Therefore, in the last few years, proteomic approaches have been used to indicate potential cytokines, chemokines, and angiogenic factors for diagnosis and/or progression of primary brain tumors [1,5,6]. Using throughput xMAP technology, Albulescu et al identified serum profiles of cytokines and angiogenic factors (IL-6, IL-1β, IL-2, IL-10, TNF-α, VEGF, FGF-2, and GM-CSF) altered in glioblastoma patients [1].…”
Section: Introductionmentioning
confidence: 99%
“…The authors highlighted that the evaluation of biomarker panels is more appropriate than single molecule analysis [1]. Studies by Popescu et al also indicated the role of simultaneous identification of proteomic signature in the diagnosis and treatment of brain tumors, as they, by means of SELDI-ToF MS technology, indicated serum S100A8, S100A9, and CXCL4 proteins as a potential candidate for glioblastoma biomarkers [5]. A bio-plex system multimarker screening by Nijaguna et al, of circulating serum biomarkers in glioma patients, indicated 18 cytokines (interleukins: -2, -3, -4, -6, -7, -10, -12, -17, -15, MIP1 α, LIF, TNF-α, FGF basic, GM-CSF, IFN-γ, IL1Rα, SCGFβ, and βNGF) discriminating glioma patients from healthy individuals [6].…”
Section: Introductionmentioning
confidence: 99%